The foreshadowing of Bangladesh : bengal muslim league and muslim politics, 1906-1947 - Harun-or-Rashid, 1954- (Dhaka : The University Press, 2003)
With reference to erstwhile Bengal, India, part of which is now Bangladesh.
Includes bibliographical references (pages [365]-372) and index.
GenEd
Keywords: Bengal Provincial Muslim League -- History; Muslims -- India -- Bengal -- Politics and government -- 20th century; Bengal (India) -- Politics and government -- 20th century